Association between obsessive-compulsive disorder severity, recurrent infections, and inflammatory markers in adults: A cross-sectional study. - Biswal, Sudhansu Priyadarsini; Pati,SaswatiSucharita; Sahoo, Duryodhan; Mahanta, Jharana (Student’s Journal of Health Research Africa, 2025)
Background Recent research suggests that obsessive-compulsive disorder (OCD) may be associated with recurrent infections and increased immune system activation. This study aims to investigate the relationship between OCD severity and the frequency of recurrent infections, along with biochemical markers of inflammation. Methods A cross-sectional observational study was conducted with 100 OCD patients, divided into two groups: those with recurrent infections and those without. Clinical data, microbiological samples, and biochemical markers (e.g., CRP, IL-6, cortisol) were collected and analyzed using statistical methods, including t-tests and correlation analyses. Results OCD patients with recurrent infections exhibited higher Y-BOCS scores (23.1 ± 4.5) compared to those without infections (20.1 ± 4.4), suggesting greater symptom severity. Staphylococcus aureus (40%), Escherichia coli (26.7%), and Streptococcus pyogenes (20%) were the most frequently isolated pathogens. Notably, patients with Streptococcus pyogenes and Staphylococcus aureus infections had higher Y-BOCS scores (28.5 ± 5.1 and 27.8 ± 4.3, respectively). Elevated IL-6 levels were significantly correlated with both OCD severity and infection frequency (β = 0.325, p = 0.009). Conclusion There is a significant association between OCD severity and recurrent infections, with inflammatory markers such as IL-6 playing a potential mediating role. These findings highlight the need for integrated psychiatric and infection control strategies in the management of OCD. Recommendation It is recommended that routine screening for infections and inflammatory markers be incorporated into the clinical assessment of OCD patients to improve treatment outcomes.